Evaluation of the influence of hydroxypropylguar gum and hyaluronic acid on physicochemical and functional characteristics of ophthalmic vehicles for olopatadine - Račić, Anđelka; Čalija, Bojan; Dobričić, Vladimir; Jurišić Dukovski, Bisera; Lovrić, Jasmina; Krajišnik, Danina (Archives of Pharmacy, 2022)
To improve ocular bioavailability of eye drops, viscosity-increasing polymers with improved functional properties have been used. The aim of this study was formulation and evaluation of viscous eye drops using vehicles containing hydroxypropyl guar gum (HPG) (0.25% w/v), sodium hyaluronate (SH) (0.4% w/v), and their combination (HPG-SH) as carriers for olopatadine (0.1% w/v). Physicochemical properties (appearance, clarity, pH, osmolality, viscosity) of the prepared formulations were tested. The drug permeability was estimated in vitro using HCE-T cell-based models and the parallel artificial membrane permeability assay (PAMPA). MTT cytotoxicity assay was performed at the end of the permeability study. Physicochemical stability of the formulated eye drops was tested during 12 months. An accelerated stability study was performed using the heating/cooling cycles test. The clarity, pH and osmolality of all formulations were in acceptable range for ophthalmic preparations. Formulation HPG-SH showed significantly higher viscosity (73.1 mPa·s) than formulations with single polymer (7.4 mPa·s for HPG i.e 3.7 mPa·s for SH) pointing to synergistic effect of polymers. The addition of polymers led to a decrease in transcorneal permeability and lower permeability coefficients with prolonged residence of drug at the ocular surface. The results of MTT assay demonstrated that the tested formulations were biocompatible and well tolerated. Formulated eye drops showed satisfactory physicochemical stability under all storage conditions. Olopatadine was successfully formulated in biocompatible viscous ophthalmic solutions. The combination of viscosity enhancer HPG with mucoadhesive polymer SH has a potential to improve precorneal residence time and therapeutic effect of olopatadine.